Efficiency of Human Resources Information System and Its Impact on The Level Effectiveness of Employees Performance Appraisal System / Practical Research on Ministry of Higher Education and Scientific Research - الزبيدي, غني دحام; عبد, هديل علي (Journal of Economics and Administrative Sciences, 2013)
AbstractThe research aims to determine the role of the efficiency of Human Resources Information System in the effectiveness of Employees Performance Appraisal System in the Ministry of Higher Education and Scientific Research / Center for the ministry, it was touching the researchers need the ministry to devise methods that employ outputs Human Resources Information System in the organization surveyed for the development of methods and levels of process evaluate the performance of its employees, in order to identify the extent of the role played by human resources information system in the process of assessing the performance of employees, we raised the question of the President as follows:(To what extent the efficiency of human resources information system? What is the impact on the level of effective staff performance appraisal system?) .May be the research community of academics and administrators owners of managerial positions within the level of middle management personnel in the Ministry of Higher Education and Scientific Research / Center for the ministry, as it has been selected sample of intentional included all heads of sections in the departments of the Ministry numbered (42), head, and the response rate (100 %). And used the questionnaire as an essential tool in the collection of data and information, and data analysis program was used (SPSS), showed results that the Ministry of Higher Education and Scientific Research employs systems, human resources information in making decisions on personnel matters, and pay attention to the quality of HR information system, but that the ministry does not employ Human Resources Information System in the process of evaluating the performance of employees, but by a few, and which fails to inform the workers on the results of evaluation of their performance, indicating a defect in the evaluation system used in the ministry, as well as having the effect of the Human Resources Information System in the level of effectiveness of the system of evaluating the performance of employees hit by the impact (83%), as well as to the existence of relations of association between the performance appraisal system and all employees of the (accuracy of the information, and the quality of human resources information system, and the use of human resources information system) ratio (55%). And left the Find a set of recommendations based on the conclusions reached by including the need to give the ministry more attention systems of information and rely on the outputs in the process of evaluating the performance of employees, to gain practical accuracy and objectivity in the evaluation results, in addition to the development of performance criteria used in assessing the performance so as to be able to Measuring the performance of employees and does not lead to the intervention of personal factors. and the need for a feedback system follows the performance appraisal process, which can be employed to identify the results of their assessment and to identify weaknesses and avoid them as well as identify the strengths and strengthened.